Working With Others: Developing Trust and Cooperation - Marilyn K. Lesmeister (EDIS)
When someone has a positive experience in a group, he/she is more likely to take risks, ask questions, and share ideas that will benefit the total group. A trusting, cooperative atmosphere doesn't happen automatically. Everyone in the group contributes to the group dynamics. When trust and cooperation exist in a group, then individuals, committees, organizations, and communities benefit. This document is FCS9212, one of a series of the Department of Family, Youth and Community Sciences. Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date August 2005.